Implementation of The Hanifida Method in Improving Public Speaking Skills - Romadlany, Zakiyah; Agustin, Anis Rohmah (Jurnal Ilmiah Syi'ar, 2024)
Public speaking is a technique of delivering messages or opinions in front of a large audience so that others can understand the information being conveyed or even change their views or opinions. Delivering information requires good speaking skills to ensure that everyone understands the message. With the rapid advancement of the times, interest in literacy has decreased, and confidence to speak in public needs to be honed.In this regard, the Al-Mawaddah area applies an easy method to sharpen students' public speaking skills using the Hanifida method, which involves reading quickly, comprehending, being intelligent, and creative. Speedreading is an activity of responding to printed or written symbols with appropriate and rapid attention.This research employs a qualitative approach with a case study design. It analyzes how the implementation of the Hanifida method can improve public speaking skills by reading and presenting the results of the readings. The findings of this study indicate that there is an improvement in public speaking skills through the implementation of the Hanifida method. This improvement is achieved through techniques such as reading, creating imagination maps, and presenting. By using this method, students become more confident, courageous, emotionally intelligent, skilled in speaking, and systematic in their thinking.